Comparison of the Effectiveness of Relational Imagery Therapy and Acceptance and Commitment Therapy on Communication Patterns in Women Experiencing Marital Infidelity - Ghasemnejad, Kiana; Sadati, Seyedeh Zahra (Psychology of Woman Journal, 2025)
Objective: The present study aimed to examine and compare the effectiveness of relational imagery therapy and acceptance and commitment therapy (ACT) on communication patterns in women confronted with marital infidelity.Methods and Materials: This research employed a quasi-experimental design with three stages (pretest, posttest, and a three-month follow-up) alongside a control group. The statistical population consisted of women aged 25 to 45 who referred to the Sina Counseling Center in Nowshahr after experiencing marital infidelity. From this population, 45 women were selected purposively and randomly assigned to three equal groups of 15: a relational imagery therapy group, an ACT group, and a control group. The Communication Patterns Questionnaire (Christensen & Sullaway, 1984) was used for data collection. Participants in the experimental groups received eight 90-minute intervention sessions twice a week. The collected data were analyzed using a mixed multivariate analysis of variance.Findings: The results demonstrated that both relational imagery therapy and acceptance and commitment therapy were effective in improving communication patterns among women facing marital infidelity. However, no significant difference was found between the two treatment groups regarding their degree of improvement.Conclusion: These findings elucidate the importance of relational imagery-based interventions in enhancing the emotional and functional indicators of women affected by marital infidelity, underscoring the necessity of employing this approach in couple counseling services.